2018
DOI: 10.1111/nin.12263
|View full text |Cite
|
Sign up to set email alerts
|

Nursing professionalization and welfare state policies: A critical review of structural factors influencing the development of nursing and the nursing workforce

Abstract: Nursing professionalization is both ongoing and global, being significant not only for the nursing workforce but also for patients and healthcare systems. For this reason, it is important to have an in-depth understanding of this process and the factors that could affect it. This literature review utilizes a welfare state approach to examine macrolevel structural determinants of nursing professionalization, addressing a previously identified gap in this literature, and synthesizes research on the relevance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 103 publications
0
19
0
5
Order By: Relevance
“…This requires a concerted global effort by all, but especially governing authorities to make this a reality, by providing legal and policy frameworks that will allow the two professions to practice to the top of their licence. However, there remains much inconsistency in the professional capabilities of the nurse and midwife between countries and regions (Gunn et al ), highlighting the need to review nursing and midwifery scopes of practice and educational preparation at national level.…”
Section: Introductionmentioning
confidence: 99%
“…This requires a concerted global effort by all, but especially governing authorities to make this a reality, by providing legal and policy frameworks that will allow the two professions to practice to the top of their licence. However, there remains much inconsistency in the professional capabilities of the nurse and midwife between countries and regions (Gunn et al ), highlighting the need to review nursing and midwifery scopes of practice and educational preparation at national level.…”
Section: Introductionmentioning
confidence: 99%
“…Our study builds on findings from a recent critical review of health and sociopolitical literature, which highlights that multifaceted links exist between professionalization and gender inequality across various socioeconomic and political domains (Gunn, Muntaner, Villeneuve, Chung, & Gea-Sanchez, 2018). We capitalize on the current scholarship preoccupied with the macro-determinants of nursing professionalization, including education and health policy initiatives (Aiken, Cheung, & Olds, 2009;Squires, Uyei, Beltran-Sanchez, & Jones, 2016), adding a new perspective, that of macro-level gender policies.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Given that a comprehensive literature review on this topic identified a number of macrolevel welfare state factors that could influence indicators of nursing professionalization, including health, education, and labour market policies (Gunn et al, 2018), in this analysis, we considered the following control factors indicators of such policies: health care spending (public/private), public coverage for health care, public education sector funding, length of maternity and paternity leaves, and trade union density rates. In addition, given that various measures of a country's economic development have been previously linked to the number of health professionals, including nurses (Squires, 2007;Wharrad & Robinson, 1999), although, in some studies, such findings did not apply to OECD countries (Currie & Carr-Hill, 2012), both gross domestic product per capita and gross domestic product annual growth rate were also considered as control variables.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Pomembno je, da imajo ne glede na strokovno področje vsi poklici skupne temeljene elemente, ki so bili prepoznani s pomočjo raziskovalnega dela (Bixler & Bixler, 1959;Schein & Kommers, 1972;Quinn & Smith, 1987;Miller, et al, 1993;Lindberg, et al, 1998;Muller, 2018;Gunn, et al, 2019). Prepoznavnost teh elementov vodi v družbeno in akademsko priznanje zdravstvene nege (Bixler & Bixler, 1959;Quinn & Smith, 1987;Miller, et al, 1993;Lindberg, et al, 1998;Skela-Savič, 2017a;Gunn, et al, 2019). Ti elementi, ki smo jih v našem prostoru na osnovi večletnega raziskovalnega dela terminološko prilagodili zdravstveni negi in so aplikativni tudi za druge zdravstvene poklice, so:…”
Section: Proučevani Okvir Profesionalizacije Zdravstvene Negeunclassified